Analisis Prediksi Kemungkinan Pergantian Auditor Pada Perusahaan Properti Dengan Menggunakan Linear Probability Model - Budiwinarto, Kim; Rahayu, Cicilia Puji; Trisnowati, Juni (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aims to analyze the prediction of the possibility of an auditor switching in property companies listed on the Indonesia Stock Exchange in 2017 based on the Public Accountant Firm’s size and management switching using a linear probability model. The data used are secondary data obtained from the financial statements of property companies. Property companies that meet the requirements in the study as a sample of 33 companies. To estimate the linear probability model using the ordinary least square method. The model that has been obtained was tested by t-test and F test. The results of the data analysis can be concluded that the model obtained can be used to predict the possibility of a property company auditor switching based on the predictor variable of Public Accountant Firm’s size and management switching with a predictive reliability level of 84.84%.  Keywords: linear probability model, auditor switching, Public Accountant Firm’s size, management switching, ordinary least square method.